Alternative dispute resolution as feasible resolution for construction disputes from the perspective of CIDB G7 contractors - Zainudin, Farah Ain (2021)
Alternative Dispute Resolution (ADR) is seen as a feasible mean of settling disputes due to its method that embraces flexibility, amicability, informality, confidentiality, overall satisfaction, direct control, optimization of minimal resources, responsiveness, speed and is low in cost. The aim of this research is to highlight ADR’s feasible features upon implementation particularly in the construction industry, reveal the CIDB G7 contractors’ perspective towards ADR and develop a framework of guideline that can be used to streamline the understanding of construction industry players on the merit of each method under ADR according to sound practices. A mixed method of research design (qualitative and quantitative) was used in the data collection phase of the study. The data obtained were analysed using descriptive analysis, Principal component analysis, content analysis, Pareto analysis, Cronbach’s alpha test and Pearson’s product moment correlation analysis. The result from the Pareto analysis showed that ‘confidentiality’ and ‘speed’ were the two (2) main pertinent feasible features of ADR that could manifest ADR as the feasible resolution for construction disputes. Other findings of the analysis which were obtained from Grade G7 contractors’ perspective have shown that ‘guideline enhancement and/or simplification’ were the most agreed enhancement mechanism of ADR to be implemented in order to encourage the implementation of ADR among the Malaysian construction industry players. The results of the study also showed that there is a positive relationship between the ADR’s feasible features and ADR’s enhancement mechanisms, which means that the result of implementing the enhancement mechanisms of ADR, more feasible features of ADR can be optimized. The relationship was used as means for the development of a new ADR’s framework which serves as the guideline for industry players particularly those in Malaysian construction industry. The contribution of this research is it offers the field of project management and Malaysian construction industry insights to the main pertinent features and enhancement mechanisms of ADR which is believed to be the means for ADR is more feasible method in resolving construction disputes compared to traditional litigation system.